2000
DOI: 10.1046/j.1365-3083.2000.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

The Primary and Memory Immune Response to Epstein–Barr Virus Infection In Vitro is Characterized by a Divergent Production of IL‐1β/IL‐6 and IL‐10

Abstract: Jabs WJ, Wagner HJ, Schlenke P, Kirchner H. The Primary and Memory Immune Response to EPSTEIN± BARR Virus Infection In Vitro is Characterized by a Divergent Production of IL-1b/IL-6 and IL-10. Scand J Immunol 2000;52:304±308 Reactivation of latent Epstein±Barr virus (EBV) infection is considered to exert substantial immunomodulating activities. Little is known about EBV's modulating activities on cytokine production upon primary, in contrast to reactivated, infection. Therefore, we investigated the cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Overall, our results are consistent with previous reports for individuals aged < 50 years, regarding the secretion of soluble IFN-γ, IL-6 and IL-10 in the presence of LCLs or lytic and latent-stage antigens (e.g. BZLF1, BMLF1, EBNA-1, EBNA-3C, LMP1, LMP2) [4,6,34,[40][41][42][43][44][58][59][60]. In contrast, the higher levels of TNF-α, IFN-γ and IL-6 found among individuals aged more than 50 years is a new observation related to EBV responses; these results suggest that individuals aged more than 50 years have an EBVcompetent immune response alongside low-grade inflammation that may emerge with age (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, our results are consistent with previous reports for individuals aged < 50 years, regarding the secretion of soluble IFN-γ, IL-6 and IL-10 in the presence of LCLs or lytic and latent-stage antigens (e.g. BZLF1, BMLF1, EBNA-1, EBNA-3C, LMP1, LMP2) [4,6,34,[40][41][42][43][44][58][59][60]. In contrast, the higher levels of TNF-α, IFN-γ and IL-6 found among individuals aged more than 50 years is a new observation related to EBV responses; these results suggest that individuals aged more than 50 years have an EBVcompetent immune response alongside low-grade inflammation that may emerge with age (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Jabs et al [58] have demonstrated that the IFN-γ and IL-10 levels produced by PBMCs depleted of T lymphocytes are decreased compared with whole PBMCs exposed to LCL supernatants, indicating the direct involvement of T lymphocytes in EBV responses. However, the presence of these cytokines in the culture supernatant cannot be attributed only to T lymphocytes, because other mononuclear cells such as monocytes may also be involved, as shown in the evaluation of the response to herpesviruses such as CMV [49].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to exert some immunomodulating activities. Reactivation of the EBV‐specific T cells leads to significant production of several cytokines, especially IFN‐γ, interleukin (IL)‐1, IL‐2 and IL‐10 (3). Additionally, the EBV BCRF1 product is a viral IL‐10 that shares high sequence homology with human IL‐10 and exerts the same activity.…”
Section: Characteristics Of All Studied Patientsmentioning
confidence: 99%
“…A possible explanation of Epstein-Barr virus mediated neural dysfunction is the activation of apoptotic pathways and intra-axonal degradation. For example, IL-1 and IL1R were found increased after EBV infection or even in nasopharyngeal carcinoma cell growth [31][32][33]. IL-1 signaling plays an important role in inflammation and early activation of host innate immune responses following virus infection [34].…”
Section: Discussionmentioning
confidence: 99%